Application of identical transformations in Cauchy problem solving - A. A. Gorshkov; E. A. Korovaytseva (Тонкие химические технологии, 2009)
A polynomial method of Cauchy problem solving is presented. The method allows constructing a fundamental solution in locally analytical form for any type of function of the right part of the equation for normal form of differential equation. A test for well-known functions both for lower and higher among possible orders of polynomial method of solving is carried out. The expediency of using the method of higher order is determined.